Deteksi Wajah Secara Real Time Menggunakan Metode Camshift - Rita Susanti; Nurul Fadillah (STMIK Budi Darma, 2019)
Face recognition research has now become a research topic that is occupied by many researchers both domestically and abroad because of the many benefits and uses of the research results. Some of the benefits of research introduce faces include security systems and robotics. Researchers introduced faces that have begun to develop the last few and have been applied mainly to security systems. Many methods can be used in face recognition, one of which is face recognition in real time using the Camshift method, Based on the results of trials on poses Having different results, In this experiment, it consisted of several tests namely testing of face detection and assessment and testing face is carried out in four types of testing, namely face recognition testing at a distance of 30 cm, face recognition testing at a distance of 50 cm, testing at a distance of 100 cm and testing using accessories.